DECISION-MAKING MODEL TO DETERMINE METHODS OF DEPLOYMENT OF THE NATIONAL GUARD OF UKRAINE FORMATIONS DURING RIOT СONTROL ACTIONS - Nazarenko О. L. (Honor and Law, 2019)
Nowadays the riot control is a challenge, and addressing it, we should give the priority to the peaceful solution of conflicts avoiding losses, casualties and threats to human life. Therefore, there is a need to search for and implement rational ways of deploying Guard’s formations, depending on the situation that develops. For determining modes of deploying of the National Guard formations, most commanders have limited time. At the same time, the growth of amount of information that they should take into account and the limited human capabilities lead to the emergence of a problematic situation in the area of decision-making. This makes it necessary to develop a model for the formation of the National Guard’s decision-making to determine the ways of deploying National Guard, taking into account its confrontation with a crowd in riots conditions. In the work, the method of deploying Guard’s formations is considered as the sequence of actions (situations, types and options of crowd actions, tactical methods and tasks of a formation). We have developed a mathematical model for determining rational ways of deploying Guard’s formations, which contributes to the qualitative fulfillment of the task of riot control by the formations of the National Guard of Ukraine.